The Influence of the Discovery Learning Model and Creative Thinking Skills on the Science Learning Outcomes of Grade IV Elementary School Students in Muntok District - Ana Mawaddah; Effendi Nawawi; Suratinah Suratinah (Edumaspul: Jurnal Pendidikan, 2025)
Education is the most important thing and plays a role in advancing the fate of a nation. Education is also the learning of knowledge, skills and habits from a group of individuals starting from generation to generation. The point is that education consists of a series of activities from one individual to another individual or in groups with guidance so that children grow and develop optimally independently and responsibly. This research aims to improve creative thinking skills, namely the discovery learning model, by implementing an experimental method. This research aims to improve creative thinking skills, namely the discovery learning model, by implementing an experimental method. The results of the study show that 1) there is a difference in the learning outcomes of science students who use the Discovery Learning model higher than those who learn using the conventional model. 2) There is an interaction between the discovery learning model and the conventional learning model reviewed from critical thinking on students' science learning outcomes. 3) There is a difference in the learning outcomes of science students who have high critical thinking skills who learn using the discovery learning model are higher than students who study with the conventional learning model. 4) There is a difference in the learning outcomes of science students who have low critical thinking who learn using the discovery learning model higher than students who study with the conventional learning model.